Pyoderma gangrenosum on the nose. Issue 5 (October 2018) - Tomioka, Takuya; Soma, Keiko; Sato, Yoichiro; Miura, Koshiro; Endo, Ayako
Abstract: Pyoderma gangrenosum is a rare ulcerative condition associated with various systemic diseases. Lesions on the lower extremities and the trunk are common, but lesions on the nose are rare. Here we report a case of pyoderma gangrenosum on the nose. A 33-year-old woman presented with fever, nasal obstruction, and painful swelling on the nasal bridge. Physical examination revealed swellings on the nasal septal mucosa bilaterally. Computed tomography showed a septal abscess and a subcutaneous abscess on the nasal bridge. The lesions worsened despite treatment with intravenous antibiotics and abscess drainage. Meanwhile, the patient also complained of bloody stools and was diagnosed with ulcerative colitis. Therefore, pyoderma gangrenosum on the nose was suspected, and was diagnosed by exclusion of other diseases. Treatment with systemic corticosteroids was started and the nasal lesions improved rapidly. However, saddle nose deformity occurred. A review of the literature reveals that pyoderma gangrenosum on the nose can cause ulcerations, septal abscess, and sinusitis. Further, there is a high likelihood of nasal complications, including saddle nose deformity, septal perforation, and skin defects. Pyoderma gangrenosum should be included in the differential diagnosis when nasal ulceration, abscesses, and sinusitis do not improve with antibiotics and drainage.